2013
DOI: 10.3109/08958378.2013.788103
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of population exposure to environmental pollutants using air quality measurements during Commonwealth Games-2010

Abstract: During the "Commonwealth Games" 2010 (CWG-2010) in Delhi, the Indian government has implemented an ambitious project "System of Air quality Forecasting And Research (SAFAR)" for monitoring and forecasting air-quality scenario. Using high-precision spatio-temporal measurements of criteria pollutants from the SAFAR network, the number of cases are estimated for total, cardiovascular and respiratory mortalities and hospital admissions. In a thinly populated airport area, the excess number of cases for total morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Most of these studies were focused on the United States and Europe and relatively little work has been devoted to India. Studies that relate air quality and human health have been performed only focusing on a few urban areas of India [ Gupta , ; Guttikunda and Goel , ; Chate et al ., ; Nagpure et al ., ] using aggregated data of local air quality. This study assesses the impact of only outdoor air quality on health for all of India on district scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies were focused on the United States and Europe and relatively little work has been devoted to India. Studies that relate air quality and human health have been performed only focusing on a few urban areas of India [ Gupta , ; Guttikunda and Goel , ; Chate et al ., ; Nagpure et al ., ] using aggregated data of local air quality. This study assesses the impact of only outdoor air quality on health for all of India on district scale.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were focused on the United States and Europe and relatively little work has been devoted to India. Studies that relate air quality and human health have been performed only focusing on a few urban areas of India [Gupta, 2011;Guttikunda and Goel, 2013;Chate et al, 2013;Nagpure et al, 2014] Burnett et al [2014], which accounts for health effect at even higher exposure concentrations. We have estimated premature mortalities due to ischemic heart disease (IHD), cerebrovascular disease (CEV, stroke), chronic obstructive pulmonary disease (COPD), and lung cancer (LC) for adult population, and acute lower respiratory illness (ALRI) for infants (<5 years old) linked to PM 2.5 exposure.…”
Section: Introductionmentioning
confidence: 99%
“…particulate matter (PM), NO X, SO 2 and CO) and CO 2 from the world's second largest sugar industry for 2014. The study quantifies and identifies the emission hot spot regions across the country and will contribute to improve emission inventories used for global/ regional chemical transport modeling for air quality studies and other applications (Pawar et al 2012 andChate et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PM not only influences global climate change, but also has been associated with adverse health and enviromnetal impacts as reported in previous studies (Gwynn et al, 2000;Husain et al, 2007;Lodhi et al, 2009;Khan et al, 2010;Stone et al, 2010;Kaushar et al, 2013;Kim et al, 2015;Pope et al, 2015). Ghude et al (2016) has reported premature mortality rate due to exposure of PM 2.5 and ozone concentration in India and Chate et al (2013) has assessed the population exposure in India due to air pollutants during Common Wealth games in 2010. Atmospheric PM that has aerodynamic diameter less than or equal to 10 µm (PM 10 ) has been studied intensively over the past few decades, because this size fraction is respirable is trapped by the alveoli of the lungs (Perez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%